Feline Atopic Skin Syndrome: an Introduction to Recently Proposed Terminology and How to Work Up the Case - Gunawan, Michael; Hardani Putra, Andhika; Widyaputri, Tiara (Acta VETERINARIA Indonesiana, 2023)
Atopic disease remains as an enigmatic hypersensitivity disorder in feline patients. Studies of cutaneous atopic syndrome in cats have reported several reaction patterns in cats, presenting as a diagnostic challenge, and a recent literature review has proposed a new set of terminologies for such diagnoses. This paper aims to report a case workup of feline atopic skin syndrome in a patient presented with severe pruritus and reaction patterns of self-inducd alopecia and facial excoriation. Feline food allergy and flea allergic dermatitis were ruled out by a 6-week elimination diet and use of fluralaner respectively. Clinical symptoms were successfully managed with the use of oral glucocorticoid (GC) and systemic and topical antimicrobial, the use of all of which for 8 weeks was deemed successful based on the degree of clinical relief provided. It is concluded that feline atopic skin syndrome is a clinical diagnosis and pharmacological interventions, including drugs to treat skin inflammation and secondary infection, are warranted.